Assessing and managing risk : an ERM perspective - Lyon, Bruce K.; Popov, Georgi (Engineer) (American Society of Safety Professionals, 2021)
"Assessing and Managing Risk: An ERM Perspective provides risk professionals and students practical guidance in the fundamentals of Enterprise Risk Management (ERM) and methods for assessing, treating, and managing risk. The entire book was designed with the reader in mind, providing practical, usable information pertinent to the risk professional"--